How artificial insemination benefits cattle farmers in Vietnam - Vu Ngoc Dung; Nguyen Thi Quynh Chi; Tran Ha; Le Thi Thanh Huyen; Marshall, Karen (International Livestock Research Institute, 2024)
This technical video, produced under the CGIAR Initiative on Sustainable Animal Productivity (2022-2024), is designed for farmers, veterinary technicians, and agricultural extension workers interested in using artificial insemination (AI) technology. It covers the key steps in the AI process, including: (1) Preparation: Selecting suitable cattle and semen, (2) Insemination: Step-by-step demonstration of the AI technique and (3) Post-Insemination Care: Ensuring cattle health and monitoring for pregnancy.